PENGARUH NET PROFIT MARGIN, CURRENT RATIO, DAN DEBT TO EQUITY RATIO PADA DIVIDEND PAYOUT RATIO - Mahendra Yasa, Kadek Dwi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study aims to determine the effect of net profit margin, current ratio and debt to equity ratioin the dividend payout ratio . Selection ofthe sample with purposive sampling method was tested with data analysis technique multiple linear regression. Population of this research are manufacturing companies listed in Indonesia Stock Exchange between 2010-2013. Samples in this study as many as 10 companies which pay dividends between 2010-2013. The results of this studys how variable net profit margin positive effecton the dividend payout ratio, variable current ratio and debt to equity ratio negatively affect the dividend payout ratio. This may implythe increase /decrease in the value of net profit margin, current ratio and debt to equity ratio will affect the increase / decrease in dividend payout ratio
Keywords: Net Profit Margin, Current Ratio, Debt to Equity Ratio, Dividend Payout Ratio